Multi-component Cycloaddition Approaches in the Catalytic Asymmetric Synthesis of Alkaloid Targets - Perreault, Stéphane (2009)
Cycloaddition reactions are attractive strategies for rapid formation of molecular complexity in organic synthesis as multiple bonds are formed in a single process. To this end, several research groups have been actively involved in the development of catalytic methods to activate readily accessible π-components to achieve cycloadditions. However, the use of C-N π-components for the formation of heterocycles by these processes is less well developed. It has been previously demonstrated that the combination of different isocyanates with two alkynes yields pyridones of several types by metal-catalyzed [2+2+2] cycloadditions. The potential of this chemistry has been extended to alkenes as C-C π-components, allowing the formation of sp(3)-stereocenters. In this tutorial review directed towards [n+2+2] cycloaddition of heterocumulenes, alkynes and alkenes, the recent advances in catalytic asymmetric synthesis of indolizidine, quinolizidine and azocine skeletons are discussed.